Transformation of Personal Prayer Spirituality amid Prayer Text Dependency in Christian Religious Education: A Case Study of Class X-10 at SMAN 4 Palangka Raya - Ciwo Ciwo; Sarmauli Sarmauli; Citra Dewi (CV. Edujavare Publishing, 2026)
This study is motivated by the phenomenon of prayer-text dependency among Christian students in Class X-10 of SMAN 4 Palangka Raya during Christian Religious Education (CRE) learning, evident in behaviors such as checking phones, reading written notes, and even writing prayer cues on their palms when asked to pray spontaneously. This study aims to describe the transformation process of students' personal prayer spirituality and to analyze how their dependency on written prayer texts influences that spiritual development. A qualitative case study approach was employed; data were collected through participant observation, in-depth interviews, Focus Group Discussions (FGD), and document study, then analyzed using the Miles and Huberman interactive model, comprising data reduction, data display, and conclusion drawing. The findings reveal that the transformation of prayer spirituality unfolds through four stages: awareness of dependency, openness to change, habituation to praying without text, and internalization of prayer as an authentic spiritual need. The study also identifies five patterns of text dependency, shaped by pedagogical, psychological, digital-technological, and theological factors, with the CRE teacher's spiritual example proving to be the primary catalyst for change. This study concludes that holistic and transformative CRE learning can shift students' prayer practice from mechanical text-reliance toward authentic personal prayer, expressing a living relationship with God. These findings are expected to serve as a reference for CRE teachers in designing more contextual and transformative approaches to teaching prayer.